2022
DOI: 10.3389/fmed.2022.900026
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Association Between COVID-19 Vaccine Hesitancy and Mental Health Status in India and Saudi Arabia—A Preliminary Evidence Collected During the Second Wave of COVID-19 Pandemic

Abstract: BackgroundVaccine hesitancy is a global public health threat. Understanding the role of psychological factors in vaccine hesitancy is often neglected and relatively less explored.Aim and ObjectivesTo analyze the relationship between mental health and COVID-19 vaccine hesitancy before and after the advent of COVID-19 vaccines (AC19V) in the general population of India and Saudi Arabia (KSA) which vary in severity of the pandemic and vaccine mandates.Materials and MethodsA total of 677 adult participants from In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 70 publications
(56 reference statements)
3
3
0
Order By: Relevance
“…It has also been shown that patients with COVID-19, comprising more non-vaxxers than vaxxers in our study, have greater mental distress than the general population 25 26. This is supported by several studies; however, others have found no discernible differences 29…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It has also been shown that patients with COVID-19, comprising more non-vaxxers than vaxxers in our study, have greater mental distress than the general population 25 26. This is supported by several studies; however, others have found no discernible differences 29…”
Section: Discussionsupporting
confidence: 89%
“…Other studies, particularly one among Israelis28 and another in Indians,29 showed negative psychological outcomes after vaccination but a bidirectional association of vaccine hesitancy and mental health among Saudis 29. In support of the causal direction of vaccine hesitancy on psychiatric outcomes, Zhang et al found that vaccine hesitancy mediated the effect of sociodemographics on anxiety and depression among their Chinese study population 30.…”
Section: Discussionmentioning
confidence: 96%
“…COVID-19 vaccine is a secret plan to reduce the population 787 ( Another factor that has proven to significantly affect acceptance rates is the vaccine's country of origin, with the majority of the population trusting the AstraZeneca vaccine of a British origin the most, followed by Pfizer-BioNTech of a US origin and Sputnik light/Sputnik V of a Russian origin; This is consistent with some studies but contrasts with others that have reported higher levels of trust in vaccines of other shown that 44% of them had severe mental disorder, 36.9% had full PTSD symptoms and 27% had both severe mental disorder and full PTSD symptoms. 26 It was reported that mental health disorders negatively affected vaccine hesitancy, 27 which could be the case in our study. Further research is required to study the mental healthspecific effects on vaccine acceptance.…”
Section: Conspiracy Theorysupporting
confidence: 64%
“…Conversely, the finding may be a spurious association. Our null findings regarding vaccine hesitancy contradict previous research revealing that higher anxiety symptom scores were associated with COVID‐19 vaccine hesitancy (Jayakumar et al ., 2022; Sekizawa, Hashimoto, Denda, Ochi, & So, 2022) and that COVID‐19 vaccine hesitancy is driven by anxiety (Palgi, Bergman, Ben‐David, & Bodner, 2021; Bullock, Lane, & LeRon, 2022).…”
Section: Discussionmentioning
confidence: 99%